1972
DOI: 10.1001/archpedi.1972.02110120051001
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Death in Midwestern Children and Youth

Abstract: Views of causes, images, and finality of death of 598 children, ages 5 to 18 years, were obtained by structured interview at church schools and clinic. The "why" of death was most affected by socioeconomic status; death as due to violence was seen most often by clinic children. The idea of what happens to the body after death was rarely terrifying, but more realism was tolerated for pets than for self. By ages 13 to 16, 20% still thought that when dead they would be cognizant, 60% envisioned spiritual continua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
1

Year Published

1973
1973
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
2
20
0
1
Order By: Relevance
“…More recent studies with American children (Gartley & Bernasconi, 1967;Kane, 1979;Koocher, 1973;McIntire, Angle, & Struempler, 1972; Townley 8c Thornburg, 1980) do not corroborate Nagy's findings with a Hungarian sample that children personif) death. This could be due to historical, cultural, or ideological differences between the two countries.…”
mentioning
confidence: 87%
“…More recent studies with American children (Gartley & Bernasconi, 1967;Kane, 1979;Koocher, 1973;McIntire, Angle, & Struempler, 1972; Townley 8c Thornburg, 1980) do not corroborate Nagy's findings with a Hungarian sample that children personif) death. This could be due to historical, cultural, or ideological differences between the two countries.…”
mentioning
confidence: 87%
“…As the sense of symbolic immortality is related psychobiologically to our existential death anxiety, symbolic immortality should be associated negatively with death anxiety. As meaning in life often has been defined as the experience of death transcendence (Frankl, 1969;Koestenbaum, 1964;Marcel, 1962), it should correlate positively with the sense of symbolic immortality and negatively with death anxiety. The specific developmental "era" of early adulthood (18 to 40 years of age) is the focus of the present study, in accordance with Lifton's theoretical assumption and empirical observation that the sense of symbolic immortality evolves throughout the life cycle.…”
mentioning
confidence: 99%
“…Furthermore, there is evidence that suicidal children have less well-developed concepts of death than other children their age, which are especially evident in a crisis situation (38,52). Investigators have found that many suicidal children are likely to view death as a transient and pleasant state (53). It is not unusual for suicidal children, who have lost loved ones, to view death as a vehicle for a happy reunion.…”
Section: Testing the Model: Developmental Differences In The Suicide mentioning
confidence: 99%